Uncommon Presentations of Axillary Artery Aneurysm - Radhika Vidyasagar; Umesh Gheewala Satish; Jithin Sony; K S Vinay; N Muralikrishna; K R Amullya; Poornima Palaniswamy; Davu Narendra Babu (Indian Journal of Vascular and Endovascular Surgery)
Background: Axillary artery aneurysms are rare compared to other peripheral aneurysms. Once developed, they can cause vascular complications like rupture, thromboembolism leading to gangrene, limb loss or neurologic complications due to their proximity to the brachial plexus. Objectives: To illustrate a variety of axillary artery aneurysms and the surgical approach used to repair them. Materials and Methods: This case series describes four cases of axillary artery aneurysms. All the cases did not have a definite aetiology. CT scan was used to diagnose the cases. All of them underwent successful surgical repair. Conclusion: Axillary artery aneurysms are rare. Because of the high incidence of symptoms and complications and the minimal morbidity associated with repair, routine operative repair should be performed.